HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG DIET DENGAN TINGKAT KECEMASAN PASIEN DIABETES MELITUS - Indriani, Shinta (STIKES Widyagama Husada, 2025)
Adherence of diabetes mellitus (DM) patients to dietary regulation and planning is a significant challenge, often influenced by stress. The duration and intensity of this stress are determined by various difficulties experienced by patients, such as dietary restrictions, the need to measure food portions, and pre-existing unhealthy eating habits prior to illness. This study aims to determine the relationship between the level of knowledge about diet and the anxiety level of diabetes mellitus patients in the Dahlia Ward of RSUD Dr. Saiful Anwar, East Java Province. This research employs a quantitative approach with a cross-sectional design, examining the relationship between two variables: the independent and dependent variables. Based on the chi-square test results using SPSS 25, the Sig (p) value = 0.263 > 0.05. This indicates that H1 is rejected, meaning there is no significant relationship between knowledge about the diabetes mellitus diet and the anxiety levels of diabetes mellitus patients in the Dahlia Ward of RSUD Dr. Saiful Anwar, East Java Province. Overall, the findings of this study show that there is no significant relationship between knowledge about diet and the anxiety levels of diabetes mellitus patients in the Dahlia Ward of RSUD Dr. Saiful Anwar. While dietary knowledge may benefit physical management, patient anxiety is more complex and requires a multidimensional approach, including psychological and social support.